A review of biochar-based catalysts for chemical synthesis, biofuel production, and pollution control. (December 2017) - Xiong, Xinni; Yu, Iris K.M.; Cao, Leichang; Tsang, Daniel C.W.; Zhang, Shicheng; Ok, Yong Sik
Graphical abstract: Highlights: Different applications demand distinctive active sites in biochar-based catalyst. Biochar as a support possesses favourable intrinsic features to assist catalysis. Biochar properties govern reactant access to active sites as the key to catalysis. Relative significance of the properties varies with the active site location. Catalytic activity of biochar can be improved by various pre- and post-treatments. Abstract: This review addresses the use of biochar as a green and versatile catalyst support for emerging high-end applications beyond soil remediation, including chemical synthesis and biodiesel production from biomass, and pollutant degradation in the environment. Their catalytic performances are comparable or even superior to the conventional resin-, silica-, or carbon-based catalysts, owing to the favourable intrinsic features of biochar (various functional groups, intricate network of structures, etc.). Yet, distinctive active sites are needed for different applications. It is highlighted that the active site accessibility for substrates critically determines the performance, which is associated with the biochar physicochemical characteristics (–SO3 H site density, pore size distribution, surface area, etc.). They show varying significance depending on the catalytic sites on biochar, which may be controlled via novel pre-/post-synthesis modifications. This review elucidates the links among catalytic performances, physicochemical properties, and pyrolysis/modification-induced features, advising the tailored production of application-oriented biochar-based catalyst in the future.